1999
DOI: 10.1093/ajcn/69.4.621
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease risk factors in 2 distinct ethnic groups: Indian and Pakistani compared with American premenopausal women

Abstract: Results suggest that these Indian and Pakistani women are at higher CVD risk than their American counterparts, but that increasing their physical activity is likely to decrease overall and regional adiposity, thereby improving their serum lipid profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 41 publications
0
55
0
Order By: Relevance
“…9 A few investigators have shown that adult South Asian and Asian Indians of both sexes have thicker truncal skinfolds than Caucasians. 30,31 Interestingly, as compared to Caucasians, greater truncal skinfold thickness in adult Asian Insulin resistance in postpubertal Asian Indian children A Misra et al…”
Section: Discussionmentioning
confidence: 99%
“…9 A few investigators have shown that adult South Asian and Asian Indians of both sexes have thicker truncal skinfolds than Caucasians. 30,31 Interestingly, as compared to Caucasians, greater truncal skinfold thickness in adult Asian Insulin resistance in postpubertal Asian Indian children A Misra et al…”
Section: Discussionmentioning
confidence: 99%
“…Lower physical activity scores have been reported in South Asians compared with white populations [89][90][91][92]. South Asians appear to ignore the beneficial effects of exercise and a lack of guidance from their physicians might partly account for this [93].…”
Section: Physical Activitymentioning
confidence: 99%
“…Elevated Lp(a) concentrations appear to promote atherothrombosis by inhibiting fibrinolysis and are associated with increased risk of CHD and stroke [139][140][141]. South Asians had higher (as much as 3-fold) concentrations of Lp(a) than whites [7,89,142]. Ethnicity was the single most important predictor for Lp(a) levels [89].…”
Section: Lipoprotein (A) (Lp(a))mentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies have reported a high prevalence of MS and cardiovascular mortality among non-resident Indians settled abroad. [4][5][6] Lifestyle factors appear to play an important role as BMI, especially abdominal obesity, and dyslipidaemia worsen with urbanization and migration. [7,8] Name The increasing prevalence of BMI and a longer life expectancy are predisposing factors for a rising incidence of type 2 diabetes mellitus coupled with CAD globally.…”
Section: Introductionmentioning
confidence: 99%